A prospective study of positron emission tomography for evaluation of neck node response 6 weeks after radiotherapy in patients with head and neck squamous cell carcinoma. (6th August 2015) - Sjövall, Johanna; Wahlberg, Peter; Almquist, Helen; Kjellén, Elisabeth; Brun, Eva
ABSTRACT: Background: The purpose of this study was to evaluate if a positron emission tomography (PET) scan, 6 weeks after radiotherapy (RT), adequately selects patients in whom a neck node dissection can be omitted. Primary endpoints were isolated neck recurrences and overall survival (OS). Methods: One hundred five patients, mainly with oropharyngeal human papillomavirus (HPV)‐positive tumors, with a positive PET scan before treatment, were evaluated regarding the neck response 6 weeks post‐RT. The PET results determined the management of the neck: observation versus neck dissection. Results: Median follow‐up was 25 months. Positive predictive value (PPV) and negative predictive value (NPV) were 56% and 94%, respectively. Four isolated neck recurrences occurred. The 2‐year OS rate was 86.3%. Conclusion: PET scans performed 6 weeks after RT have a high NPV and can obviate neck dissections but the PPV is insufficient. A later scheduled scan is recommended. © 2015 Wiley Periodicals © 2015 Wiley Periodicals, Inc. Head Neck 38 : E473–E479, 2016